2017
DOI: 10.1101/gad.305250.117
|View full text |Cite
|
Sign up to set email alerts
|

Non-AUG translation: a new start for protein synthesis in eukaryotes

Abstract: Although it was long thought that eukaryotic translation almost always initiates at an AUG start codon, recent advancements in ribosome footprint mapping have revealed that non-AUG start codons are used at an astonishing frequency. These non-AUG initiation events are not simply errors but instead are used to generate or regulate proteins with key cellular functions; for example, during development or stress. Misregulation of non-AUG initiation events contributes to multiple human diseases, including cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
336
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(360 citation statements)
references
References 189 publications
(262 reference statements)
20
336
3
1
Order By: Relevance
“…Consistent with this, we and others observed that exogenous stressors or eIF2a phosphorylation selectively enhances RAN translation at both CGG repeats and GGGGCC repeats associated with ALS [30,32,39] in a near-AUG codon-dependent manner. Several other eIFs are known to modulate start codon fidelity [33,81]. eIF1 maintains the fidelity of scanning 43S PICs for AUG start codons by antagonizing the structural reconfigurations that follow AUG recognition [58,[60][61][62][63].…”
Section: Bel/ddx3x Selectively Modulates Fmr1 Ran Translation In Humamentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this, we and others observed that exogenous stressors or eIF2a phosphorylation selectively enhances RAN translation at both CGG repeats and GGGGCC repeats associated with ALS [30,32,39] in a near-AUG codon-dependent manner. Several other eIFs are known to modulate start codon fidelity [33,81]. eIF1 maintains the fidelity of scanning 43S PICs for AUG start codons by antagonizing the structural reconfigurations that follow AUG recognition [58,[60][61][62][63].…”
Section: Bel/ddx3x Selectively Modulates Fmr1 Ran Translation In Humamentioning
confidence: 99%
“…A key feature that distinguishes RAN translation from canonical translation is its use of non-AUG codons for initiation [10,[30][31][32]. The specificity for AUG start codons is simultaneously (and paradoxically) central to the integrity of eukaryotic and prokaryotic proteomes and an essential point of regulation for determining which, when, and how much protein is synthesized from a given mRNA transcript [81,[99][100][101][102]. RNA secondary structure-forming elements (including GC-rich NREs) are predicted to slow or stall Data information: For all panels, ****P ≤ 0.0001 for the specified statistical test (compiled from ≥ 3 replicates).…”
Section: A the Expression Of Plasmid-based Nl-3xf Reporters In Hek293mentioning
confidence: 99%
“…Leaky scanning also occurs on non‐uORF containing mRNAs and can act as a mechanism for alternative start codon selection, whereby a portion of ribosomes initiate at a downstream, in‐frame start codon. Most ORFs initiate with AUG start codons, although there is increasing evidence of initiation at other start codons, albeit often at a reduced frequency (Kearse & Wilusz, ). Several N ‐terminally extended proteins have been observed by ribosome footprinting following oxidative stress (Gerashchenko et al, ).…”
Section: Mrna‐specific Regulation: Roles Of Mrna Elementsmentioning
confidence: 99%
“…Recent ribosome footprinting experiments have revealed that thousands of non‐AUG codons are used as start codons for translation initiation genome‐wide . Selection of the appropriate start codon for initiation is a regulated process, involving eIF1, eIF1A, eIF2, eIF3, and eIF5 . Alterations in levels, stoichiometry, or activity of these factors can alter start codon selection.…”
Section: How Cellular Stress Affects Translationmentioning
confidence: 99%